An activated Q‐SNARE/SM protein complex as a possible intermediate in SNARE assembly. (8th May 2017) - Jakhanwal, Shrutee; Lee, Chung‐Tien; Urlaub, Henning; Jahn, Reinhard
Abstract: Assembly of the SNARE proteins syntaxin1, SNAP25, and synaptobrevin into a SNARE complex is essential for exocytosis in neurons. For efficient assembly, SNAREs interact with additional proteins but neither the nature of the intermediates nor the sequence of protein assembly is known. Here, we have characterized a ternary complex between syntaxin1, SNAP25, and the SM protein Munc18‐1 as a possible acceptor complex for the R‐SNARE synaptobrevin. The ternary complex binds synaptobrevin with fast kinetics, resulting in the rapid formation of a fully zippered SNARE complex to which Munc18‐1 remains tethered by the N‐terminal domain of syntaxin1. Intriguingly, only one of the synaptobrevin truncation mutants (Syb1‐65) was able to bind to the syntaxin1:SNAP25:Munc18‐1 complex, suggesting either a cooperative zippering mechanism that proceeds bidirectionally or the progressive R‐SNARE binding via an SM template. Moreover, the complex is resistant to disassembly by NSF. Based on these findings, we consider the ternary complex as a strong candidate for a physiological intermediate in SNARE assembly. Synopsis: The ternary complex syntaxin1, SNAP25a and Munc18‐1 acts as an intermediate in the SNARE assembly pathway by functioning as an acceptor for synaptobrevin/VAMP‐2. Syntaxin1:SNAP25:Munc18‐1 complex acts as an efficient acceptor complex for synaptobrevin‐binding. Synaptobrevin binding to this complex leads to major structural rearrangements, with Munc18‐1 being tethered to the N‐terminus of syntaxin1 in a fully‐zippered SNARE complex. Syntaxin1:SNAP25:Munc18‐1 complex is resistant to disassembly by NSF‐αSNAP. A full‐length synaptobrevin fragment is required to efficiently bind to the syntaxin1:SNAP25:Munc18‐1 complex. Abstract : The ternary complex syntaxin1, SNAP25a and Munc18‐1 acts as an intermediate in the SNARE assembly pathway by functioning as an acceptor for synaptobrevin/VAMP‐2.